Produksi Bioetanol Dari Limbah Kulit Kopi Menggunakan Enzim Zymomonas Mobilis Dan Saccharomyces Cereviseae - Saisa .; Maliya Syabriana (Jurnal Serambi Engineering, 2018)
The availability of coffee leather waste is quite large in Aceh, because coffee processing will produce 65% coffee beans and 35% of coffee leather waste, while coffee production in Central Aceh in 2013 reaches a total of 26 thousand tons. Coffee skin waste has fiber content of 65.2%. The purpose of this study is expected to create a new source of renewable energy that is environmentally friendly and can overcome the scarcity of fuel. The process of making bioethanol is done by hydrolyzing the waste of coffee skin into glucose using HCl catalyst. Furthermore, glucose is fermented into bioethanol using Saccharomyces cereviseae and Zymomonas Mobilis bacteria. The variables performed were fermentation time of 5, 7 and 9 days, starter concentration 5%, 10% and 15% and ratio of enzyme combination of Saccharomyces cereviseae and Zymomonas mobilis (1: 2, 1: 1, 2: 1). This study is expected to find the best yield and ethanol content when compared with no enzyme combination